The Influence of Acceptance of LGBT Groups in Thailand on LGBT Social Movements in Indonesia - Attara, Sephia Caesaria; Tyas, Intan Kinanthi Damarin; Amin, Khoirul; Paramitha, Devy Indah (CV. Publikasi Indonesia, 2024)
This research aims to examine the influence of acceptance of LGBT people in Thailand on the development of LGBT social movements in Indonesia, as well as identify the challenges faced by LGBT people in Indonesia. Using the New Social Movement and Network Social Movement approaches, this research explores the role of social networks and the cultural, religious, and traditional factors that influence public acceptance of LGBT people in both countries. A qualitative method with a descriptive approach was used to analyze secondary data obtained from various sources, including official documents, books, scientific journals, and previous research reports. The results show that LGBT acceptance in Thailand, influenced by cultural values and Buddhism, has created a more inclusive environment for LGBT people. More inclusive policies, such as anti-discrimination laws, as well as positive representations of LGBT people in the media and popular culture in Thailand, triggered the emergence of social movements supporting LGBT rights in Southeast Asia, including in Indonesia. However, in Indonesia, LGBT social movements face greater challenges due to the strong cultural and religious traditions of conservative Islam. As a result, it has been difficult for LGBT social movements to gain widespread acceptance, and discrimination and stigma against LGBT people remain strong. Nonetheless, the positive influence of Thailand helps motivate LGBT activists in Indonesia to continue fighting for their rights through advocacy, campaigns and public education.